DEVELOPMENT OF MULTIPLE-CHOICE QUESTION INSTRUMENTS BASED ON GOOGLE FORM ON ENVIRONMENTAL POLLUTION MATERIALS FOR CLASS VII JUNIOR HIGH SCHOOL - Zulfa Zulfa; Lina Arifah Fitriyah; Nur Kuswanti (Jurnal Pembelajaran Sains, 2021)
This research is included in development research with the objectives of this study (1) to describe the process of developing a google form-based question instrument at each ADDIE stage, and (2) to describe the product developed after the validation process. This study used the ADDIE development model, with stages of Analyze, Design, Development, Implementation, and Evaluation. Data were obtained from; (1) descriptive data on the process of developing a google form-based question instrument and (2) quantitative data from the validation results from the validator and empirical test results in the form of item validity, reliability, level of difficulty, discriminating power, and distractors. The result showed that there were 7 out of 10 questions that were declared valid, the reliability value was 0.740 with a high level of reliability, the descriminatory power showed that there were 8 questions that were said t be good, 1 question was accepted and had to be revised and 1 question was rejected, from 10 questions there were 6 questions that were declared easy and 4 while, there were 11 out of 40 answer options which were declared not to function as distractors.